Getting back on track: Development of a blended-care intervention for weight recurrence after metabolic bariatric surgery using intervention mapping - Vera Voorwinde; Ingrid H.M. Steenhuis; Ignace M.C. Janssen; Valerie M. Monpellier; Maartje M. van Stralen (PEC Innovation)
Objective: To systematically re-develop a blended-care intervention addressing weight recurrence after metabolic bariatric surgery (MBS). Weight recurrence poses a significant longterm challenge for around 20–30 % of MBS patients. The intervention aims to improve weight outcomes and enhance patient well-being. This study describes the novel application of the Intervention Mapping (IM) protocol, integrating scientific evidence and stakeholder input. Methods: The six-step IM protocol guided the development process, ensuring the active involvement of patients and healthcare professionals. A comprehensive needs assessment using quantitative, qualitative, and literature-based approaches informed the creation of a logic model of the problem (Step 1) and a logic model of change (Step 2). Program outcomes and objectives were formulated through collaborative brainstorming and design-thinking sessions, leading to intervention design (Step 3). The intervention was co-produced with patients, implementers, and an app developer (Step 4). Detailed implementation (Step 5) and evaluation (Step 6) plans were subsequently developed. Results: The IM process yielded a blended-care intervention grounded in theoretical frameworks and evidence-based methods. The intervention actively involved the target population and implementers, addressing key determinants of weight recurrence. Conclusion: The IM protocol demonstrated utility in designing a tailored, theory-based intervention post-MBS. The process emphasized the value of integrating stakeholder perspectives and highlighted the feasibility of co-creating an evidence-informed intervention. Innovation: This intervention incorporates newly developed elements in a novel blended-care structure. Future evaluation is necessary to determine its effectiveness in achieving the desired outcomes.